Do cerebral arteriovenous malformations increase in size?. Issue 8 (August 1987) - Mendelow, A D; Erfurth, A; Grossart, K; Macpherson, P
Abstract : Six patients are reported with cerebral arteriovenous malformations which have enlarged over follow up periods of from 4 to 20 years. The frequency of spontaneous enlargement is estimated to range from 0.2% to 2.8% per annum. This rate of enlargement should be considered when treatment options are reviewed in individual patients, and should be added to the risk of haemorrhage.